Mapping Scientific Argumentation Profile of Prospective Biology Teachers as Basis for Readiness for 21st Century Skills Oriented to STEM Learning - Desi Eka Nur Fitriana; Ika Rifqiawati; Indah Juwita Sari (Universitas Tidar, 2026)
Scientific argumentation is one of the key competencies in 21st-century science learning that must be mastered by prospective biology teachers. This study aims to map the profile of prospective biology teachers' scientific argumentation abilities based on the level of argumentation quality and the achievement of each indicator. This study used a quantitative approach with a descriptive design. The subjects were prospective biology teacher students selected through purposive sampling. The research instrument was a scientific argumentation test based on a biology context developed based on the Claim, Data, Warrant, Support, and Rebuttal framework. Data were analyzed descriptively by converting scores into percentages and mapping them to scientific argumentation Levels 1–5. The results showed that the Claim indicator achieved the highest percentage of 59%, while the Data (43%), Warrant (43%), Backing (41%), and Rebuttal (41%) indicators were in the lower category. Based on the mapping level, the scientific argumentation abilities of prospective general biology teachers were generally at Level 3 (fairly developed), with a tendency for some students to remain at Level 2, particularly in the components of scientific reasoning, strengthening theory, and developing rebuttals. These findings serve as recommendations for the implementation of STEM learning to strengthen scientific argumentation. Keywords: 21st Century Skills, biology education, scientific argumentation, prospective biology teacher, STEM Education